2008
DOI: 10.1002/ajh.21197
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acute graft‐versus‐host disease following reduced‐intensity stem‐cell transplantation from an HLA‐identical related donor

Abstract: To investigate clinical features of acute graft-versus-host disease (GVHD) following reduced intensity stemcell transplantation (RIST), we retrospectively investigated medical records of 65 patients with hematologic malignancies who underwent RIST from a matched related donor. Preparative regimen comprised fludarabine 30 mg/m 2 (n 5 53) or cladribine 0.11 mg/kg (n 5 12) for 6 days plus busulfan 4 mg/kg for 2 days. Twelve patients received rabbit antithymocyte globulin 2.5 mg/kg/day for 2-4 consecutive days. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
1
1
1
Order By: Relevance
“…With regard to aGvHD, we found a GIT rather than skin to be the most frequently affected site; this differs from the findings following MAC HSCT where skin is the most frequently affected site [31]. Relatively few studies have described the tissue site of GvHD in detail following RIC HSCT, but following purine analogue-based conditioning aGvHD is reported to affect the skin in 58-75% and GIT in 50-56% of cases [9,10,32]. Thus, we report a slightly higher incidence of GIT GvHD with a relatively reduced incidence of cutaneous GvHD.…”
Section: Discussioncontrasting
confidence: 58%
“…With regard to aGvHD, we found a GIT rather than skin to be the most frequently affected site; this differs from the findings following MAC HSCT where skin is the most frequently affected site [31]. Relatively few studies have described the tissue site of GvHD in detail following RIC HSCT, but following purine analogue-based conditioning aGvHD is reported to affect the skin in 58-75% and GIT in 50-56% of cases [9,10,32]. Thus, we report a slightly higher incidence of GIT GvHD with a relatively reduced incidence of cutaneous GvHD.…”
Section: Discussioncontrasting
confidence: 58%
“…note, the validation study has demonstrated the association between the recipient 197A genotype and the increased incidence of chronic GVHD. This might reflect the association between the recipient 197A genotype and the risk of late acute GVHD, 49 considering that late acute GVHD occurs frequently after nonmyeloablative conditioning transplantation 50 and that the manifestation of late acute GVHD is usually indistinguishable from chronic GVHD. 51 In this study, the diagnosis of chronic GVHD was based on historical criteria, 45 and data on chronic GVHD classification according to the new NIH criteria 49 were unavailable, thus suggesting that late-onset, prolonged or delayed acute GVHD could have been diagnosed as chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha encontrado que, entre hermanos con HLA idéntico que reciben un trasplante alogénico, la incidencia de la enfermedad aguda es mucho más baja, alrededor del 20 %, que entre aquellos que reciben varios injertos no relacionados 12,13 . La incidencia de enfermedad aguda de injerto contra huésped de grado III/IV es de 30 % en donantes no relacionados con HLA idéntico, de 40 % en aquellos con una disparidad en uno o dos alelos de la clase I, especialmente HLA-A, y de, aproximadamente, 33 % cuando se trata de trasplantes de familiares pero con disparidad en uno o dos alelos [14][15][16] . Figura 1.…”
Section: Enfermedad Aguda De Injerto Contra Huéspedunclassified